Large-scale atomic data calculations in Ce V – X ions for application to early kilonova emission from neutron star mergers. Issue 4 (26th November 2021) - Carvajal Gallego, H; Berengut, J C; Palmeri, P; Quinet, P
ABSTRACT: New radiative parameters (wavelengths, transition probabilities, and oscillator strengths) are reported in the present paper for a large number of spectral lines in moderately charged cerium ions, from Ce V to Ce X. These results were obtained through large-scale atomic structure calculations carried out using three different and independent theoretical approaches, namely the relativistic Hartree–Fock method, including core-polarization corrections (HFR + CPOL), the multiconfiguration Dirac–Hartree–Fock method, and the Particle-Hole Configuration Interaction (PH-CI) method implemented in the AMBiT code. The accuracy of the results was assessed through detailed comparisons between the data deduced from these methods and with the few theoretical and experimental data previously published. For the six cerium ions considered, the most complete and reliable sets of transition wavelengths and rates were then used to calculate the expansion opacities characterizing the early phases of kilonovae following neutron star mergers, i.e. for typical conditions corresponding to temperatures T > 20 000 K, a density ρ  = 10 −10  g cm −3 and a time after the merger t  = 0.1 d.